2003
DOI: 10.1081/dis-120025544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino‐Acid‐Based Polar Oils on the Krafft Temperature and Solubilization in Ionic and Nonionic Surfactant Solutions

Abstract: The Krafft temperature and solubilization power of ionic and nonionic surfactants in aqueous solutions are strongly affected by added polar oils such as amino-acid-based oils (e.g., N-acylamino acid esters, AAE), because they tend to be solubilized in the surfactant palisade layer. The Krafft temperatures of 5 wt.% sodium dodecyl sulfate (SDS)-water and octaoxyethylene octadecyl ether (C 18 EO 8 )-water systems largely decreases upon addition of AAE and 1-hexanol, whereas it decreases very slightly in isopropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…likely to behave as polar or non-polar oil depend on the occasion. We had found that this semi-polar oil behaves as co-surfactant in the polyoxyethylene-type nonionic surfactant (C 12 EO 8 ) [1][2][3] and sodium dodecyl sulfate (SDS) systems [3,4]. Afterwards, however, it was demonstrated that the solubilization sites of SLIP varies with its concentration in a homologous amino acid surfactant system: SLIP penetrates into the palisade layer at its low concentration, but further addition of SLIP leads to the solubilization in the micelle core [4].…”
Section: Introductionmentioning
confidence: 99%
“…likely to behave as polar or non-polar oil depend on the occasion. We had found that this semi-polar oil behaves as co-surfactant in the polyoxyethylene-type nonionic surfactant (C 12 EO 8 ) [1][2][3] and sodium dodecyl sulfate (SDS) systems [3,4]. Afterwards, however, it was demonstrated that the solubilization sites of SLIP varies with its concentration in a homologous amino acid surfactant system: SLIP penetrates into the palisade layer at its low concentration, but further addition of SLIP leads to the solubilization in the micelle core [4].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that the addition of SLIP causes the different type of phase transition in the SDS/water system and in the Sar/water system 4) . In the hexagonal liquid crystal phase (H 1 ), SLIP penetrates in the palisade layer of the surfactant for both systems.…”
mentioning
confidence: 98%
“…and sodium dodecyl surfate (SDS) systems 4) to cause the phase transition from hexagonal liquid crystal (H 1 ) to lamellar liquid crystal phase (La); the use of SLIP as a cosurfactant in various applications seemed to be very promising. However, it was demonstrated that the solubilization sites of SLIP varied with its concentration in the homologous sodium N-dodecanoyl sarcosinate (or sodium N-dodecanoyl-N-methylglycinate, Sar) system 5) .…”
mentioning
confidence: 99%